Scale law of complex deformation transitions of nanotwins in stainless steel - A. Y. Chen (Nature Portfolio, 2019)
The deformation mechanisms of twin boundaries in nanotwinned metallic materials are still unclear. Here the authors combine in situ transmission electron microscopy tensile tests and molecular dynamics simulations with a dislocation-based theoretical model to reveal the deformation mechanism of nanotwins.